2009
DOI: 10.1016/j.jnoncrysol.2009.04.046
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Ga incorporation on photoinduced phenomena in Ge–S based glasses

Abstract: a b s t r a c tTo study the influence of Ga addition on photoinduced effect, GaGeS glasses with constant atomic ratio S/Ge = 2.6 have been prepared. Using Raman spectroscopy, we have reported the effect of Ga on the structural behavior of these glasses. An increase of the glass transition temperature T g , the linear refractive index and the density have been observed with increasing gallium content. The photoinduced phenomena have been examined through the influence of time exposure and power density, when ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…These works also use several different methods such as Raman [12,[36][37][38][39], XAFS [40], neutron diffraction [41], EXAFS [42], XRD and Raman [43], 2D micro-Raman [44]. They have all found that Ge and Ga atoms are equally fourfold coordinated, [GaS 4 ] and [GeS 4 ] tetrahedral units are cross-linked via bridging sulfur atoms, M-chalcogen bonds are preferable.…”
Section: Introductionmentioning
confidence: 99%
“…These works also use several different methods such as Raman [12,[36][37][38][39], XAFS [40], neutron diffraction [41], EXAFS [42], XRD and Raman [43], 2D micro-Raman [44]. They have all found that Ge and Ga atoms are equally fourfold coordinated, [GaS 4 ] and [GeS 4 ] tetrahedral units are cross-linked via bridging sulfur atoms, M-chalcogen bonds are preferable.…”
Section: Introductionmentioning
confidence: 99%
“…Fig. 5A, B and C, belongs to the stretching of S-S bonds in S n chains or S 8 rings, see for instance [8,14]. The RF(470) can probably be assigned to the bending modes of Ge-O-Ge (≈556 cm −1 ) or to the breathing motion of oxygen in the GeO 4 ring (≈520 cm −1 ) [20] if a disorder in the film network, the inclusive presence of S x O 3−x Ge-O-GeO 3−x S x units, leads to an increase in the Ge-O-Ge valence angle, to a decrease in corresponding force constants and hence to the shift of this RF by about 60 cm −1 to the lower wavenumber.…”
Section: The Changes Induced By Uv Photon Illuminationmentioning
confidence: 99%
“…For photoexpansion in Ge-S binary glasses, the presence of Ga atoms is suggested to be essential because just photooxidation leads to formation of (Ge/Ga)-O units inducing photoexpansion [8]. From a number of studies it is evident that (i) the blue light supports photooxidation of amorphous chalcogenide films and (ii) photooxidation of amorphous chalcogenides is an interesting process which could significantly and dynamically modify the surface, near surface states and even, depending on the actual conditions of photooxidation, the volume properties of the films [3][4][5][6][7][8]. Moreover, it seems that compositional and structural changes associated with photooxidation "can be applied to in situ formation of materials with a new structural organization" [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many experimental techniques to study the atomic void structure of solids, but they are lim-ited at the sub-nanometer scale [8][9][10][11]. One of the informative tools used to identify and study internal free volumes in various materials is positron annihilation lifetime (PAL) spectroscopy [12,13].…”
Section: Introductionmentioning
confidence: 99%